Perancangan Proteksi Katodik pada Tangki Olein Kapasitas 450 KL dengan Metode SACP: -- - Wardani, Dianita -; Prasojo, Budi (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
Cathodic protection is needed as corrosion mitigation in oil tanks on land to minimize internal and external corrosion. Corrosion problems that often arise in tanks are corrosion on the shell, roof and bottom. In this research, a corrosion protection system was designed for an olein storage tank with a capacity of 450 kL for one of the palm oil ship industries located in Kalimantan. The corrosion protection used is SACP (Sacrificial Anode Cathodic Protection) where active anodes are used to protect metal surfaces which are more passive against corrosion attacks. To provide good corrosion protection, sufficient current, number of anodes and correct placement are required. From the calculation results it was found that for the shell, the current required is 0.0102446 A with a total of 46 anodes and the placement of each anode is 5.36 m. For the same bottom and roof, each requires a current of 0.0103869 A with 7 anodes and a distance within a radius of 6.74 m.